Keperluan Media Poster pada Materi Adab Jual Beli Online di Kelas X MA Darul Ulum - Aspiani, Ahmad; Kastalani, Akhmad (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to develop poster media on the material of adab buying and selling online in class X MA Darul Ulum. The research method used is Research and Development (R&D) with data collection techniques through observation, questionnaires / surveys, interviews, and documentation. The research subjects were class X students totaling 27 people. The results showed that the use of poster media in learning fiqh buying and selling material at MA Darul Ulum Palangka Raya was in the very effective category. This can be seen from two indicators, namely: (1) The effectiveness of poster learning media obtained a percentage of 72%, and (2) The effectiveness of buying and selling material obtained a percentage of 72%. Thus, it can be concluded that the use of poster media in learning fiqh buying and selling material at MA Darul Ulum Palangka Raya is very effective